Gene silencing in adipose tissue macrophages regulates whole-body metabolism in obese mice - Aouadi, Myriam; Tencerova, Michaela; Vangala, Pranitha; Yawe, Joseph C.; Amano, Shinya U.; Czech, Michael P. (Proceedings of the National Academy of Sciences, 2013)
Adipose tissue (AT) inflammation and infiltration by macrophages is associated with insulin resistance and type 2 diabetes in obese humans, offering a potential target for therapeutics. However, whether AT macrophages (ATMs) directly contribute to systemic glucose intolerance has not been determined. The reason is the lack of methods to ablate inflammatory genes expressed in macrophages specifically localized within AT depots, leaving macrophages in other tissues unaffected. Here we report that i.p. administration of siRNA encapsulated by glucan shells in obese mice selectively silences genes in epididymal ATMs, whereas macrophages within lung, spleen, kidney, heart, skeletal muscle, subcutaneous (SubQ) adipose, and liver are not targeted. Such administration of GeRPs to silence the inflammatory cytokines TNF-α or osteopontin in epididymal ATMs of obese mice caused significant improvement in glucose tolerance. These data are consistent with the hypothesis that cytokines produced by ATMs can exacerbate whole-body glucose intolerance.
Keywords: Obese mice; Gene silencing; Macrophages